Cost-Benefit Analysis of Conventional and Modern Vegetable Farming in Bhaktapur District - Adhikari, Tara Prasad; Chalise, Dhan Raj (The EFFORTS, Journal of Education and Research, 2025)
This study aims to evaluate the cost-benefit analysis (CBA) of modern versus conventional vegetable farming in the Bhaktapur District, addressing gaps in existing research that often favor controlled or organic farming without a clear comparison to modern methods. Using a multistage sampling procedure, data were collected from 50 farmers (25 conventional, 25 modern) across Madhyapur Thimi and Suryabinayak municipalities, focusing on three key vegetables: tomato, cauliflower, and radish. Despite higher input costs, modern farming methods have significantly increased crop yields and farmer income. Among the crops studied, cauliflower was the most profitable under both systems, with Benefit-Cost Ratios (BCR) of 3.71 for conventional and 4.12 for modern farming. Tomato also showed strong profitability (BCR: 2.83 conventional, 3.08 modern), while radish, though less profitable, offered quicker harvest cycles and lower risk, making it attractive for small-scale farmers. The findings suggest that prioritizing crops with stable returns, alongside optimized farming techniques, can substantially improve productivity, profitability, and sustainability in Bhaktapur’s agricultural sector. To facilitate this transition, the study recommends that federal and provincial governments offer financial incentives such as loans and grants, enabling smallholder farmers to adopt modern practices like tunnel farming and precision agriculture. Such support would enhance long-term agricultural sustainability and strengthen the livelihoods of vegetable farmers in the district.